2020
DOI: 10.3390/microorganisms8020240
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Kazachstania humilis Yeast Species and Lactic Acid Bacteria in Sourdough

Abstract: Sourdoughs harbor simple microbial communities usually composed of a few prevailing lactic acid bacteria species (LAB) and yeast species. However, yeast and LAB found in sourdough have been described as highly diverse. Even if LAB and yeast associations have been widely documented, the nature of the interactions between them has been poorly described. These interactions define the composition and structure of sourdough communities, and therefore, the characteristics of the final bread product. In this study, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(37 citation statements)
references
References 50 publications
(87 reference statements)
4
33
0
Order By: Relevance
“…In particular, S. cerevisiae IMA D4Y, D17Y and D25Y showed a www.nature.com/scientificreports/ significant higher leavening performance than S. cerevisiae commercial baker's yeast in doughs obtained using wheat flours, highlighting their efficiency as leavening agents. Similar results were found by Carbonetto et al 39 , who reported that K. humilis strains never leavened dough as much as S. cerevisiae when singly inoculated in doughs. Moreover, our results showed that, contrary to S. cerevisiae commercial baker's yeast, 33% of strains were able to increase the volume of doughs made using barley, which is a cereal with a lesser ability to form a gluten complex than wheat, thus decreasing dough gas retention 40 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In particular, S. cerevisiae IMA D4Y, D17Y and D25Y showed a www.nature.com/scientificreports/ significant higher leavening performance than S. cerevisiae commercial baker's yeast in doughs obtained using wheat flours, highlighting their efficiency as leavening agents. Similar results were found by Carbonetto et al 39 , who reported that K. humilis strains never leavened dough as much as S. cerevisiae when singly inoculated in doughs. Moreover, our results showed that, contrary to S. cerevisiae commercial baker's yeast, 33% of strains were able to increase the volume of doughs made using barley, which is a cereal with a lesser ability to form a gluten complex than wheat, thus decreasing dough gas retention 40 .…”
Section: Discussionsupporting
confidence: 90%
“…Similar results were found by Carbonetto et al . 39 , who reported that K. humilis strains never leavened dough as much as S. cerevisiae when singly inoculated in doughs. Moreover, our results showed that, contrary to S. cerevisiae commercial baker’s yeast, 33% of strains were able to increase the volume of doughs made using barley, which is a cereal with a lesser ability to form a gluten complex than wheat, thus decreasing dough gas retention 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Distinct microbial ecosystems are created in Type I sourdoughs. The metabolic diversity of two groups of microorganisms, yeasts and bacteria, enables a wide range of interactions and associations [ 5 , 6 ] that greatly affect the performance of the dough, the nutritional properties, and the overall quality of sourdough breads, including the microbial shelf life [ 7 , 8 ] and functional properties [ 9 , 10 ]. Sourdoughs are widely used to produce “slow breads” (long fermentation time) and “low FODMAP breads” (Fermentable Oligosaccharides, Disaccharides, Monosaccharides, and Polyols), which are increasingly appreciated by consumers due to their nutritional and sensory qualities and effect on human health [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In sourdough B, four strains belonged to the S. cerevisiae species, while the other strains belonged to K. humilis species (Table 1). These two species represent typical yeast interactions found in other traditional sourdoughs [12,14]. Furthermore, as demonstrated by Fujimoto et al [15], the reduced fermentation of sourdough could favor the dominance of S. cerevisiae, as happened in sourdough B.…”
Section: Yeasts Molecular Characterizationmentioning
confidence: 74%